ANALYSIS OF THE IMPACT OF UNDERSTANDING TAXATION RULES, FISCUS SERVICE QUALITY, AND TAX SANCTIONS ON PERSONAL TAX COMPLIANCE COMPLIANCE WITH RISK PREFERENCE AS MODERATED VARIABLES - Anik Yuesti; Made Sudiartana (AIBPM Publisher, 2019)
Tax is a compulsory contribution owed to the State by an individual or an entity that is a force based on the Law that does not receive compensation directly but is used for State purposes, namely the prosperity of the people. This study aims to examine the understanding of tax regulations, quality of tax authorities services, and tax sanctions on individual taxpayer compliance, and risk preferences which act as moderating variables. The data in this study were obtained from the questionnaire (primary). The population in this study amounted to 85,781 people. The method of determining the sample in this study is the accidental sampling method and using the Slovin formula so that it gets the number of 100 people. The data analysis technique used is (Moderated Regression Analysis) and factor analysis. The results showed that understanding of tax regulations, quality of tax authorities services, and tax sanctions had a positive effect on taxpayer compliance while risk preferences did not affect taxpayer compliance. Risk preference shows the results of not being able to moderate the relationship between understanding tax regulations, the quality of tax services, and tax sanctions on taxpayer compliance.